Keefektifan Teknik Mutual Stoytelling untuk Meningkatkan Motivasi Belajar Siswa SD - Fitriyani Fitriyani; Asrowi Asrowi; Rian Rokhmad Hidayat (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This research aimed to test the effectiveness of mutual storytelling technique to improve the motivation to learn of fifth grade students. This research was a Time Series Design that consist of one group. The research subjects were six students selected using purposive sampling technique. The technique of collecting data using questionnaire. Data analysis using the Wicoxon Signed Rank test. Based on the result of the analisis using Wilcoxon Signed Rank Test, it showed that the significance value is 0,027 (0,027<0,05). So there is a difference between before and after given treatment to students. The conclusion of the research was that mutual storytelling technique was effective to improve the motivation to learn of fifth grade students. The result of this research could be used by classroom teachers as a reference to deepen the understanding of the implementation of mutual storytelling technique to improve motivation of learn for students. It could also be used as a reference for other researchers to innovate to conduct research using mutual storytelling techniques in other service fields.Abstrak : Tujuan penelitian ini adalah untuk mengetahui keefektifan teknik mutual storytelling untuk meningkatkan motivasi belajar peserta didik kelas lima SD. Penelitian ini menggunakan Time Series Design yang terdiri dari satu kelompok. Subjek penelitian berjumlah 6 peserta didik yang dipilih menggunakan teknik purposive sampling. Teknik pengumpulan data menggunakan angket. Analisis data menggunakan uji Wilcoxon Signed Rank Test. Berdasarkan hasil analisis uji Wilcoxon Signed Rank Test menunjukkan nilai signifikansi 0,027 (0,027<0,05). Dengan demikian, dapat diketahui bahwa ada perbedaan antara sebelum dan sesudah diberikan treatment pada peserta didik. Simpulan dari hasil penelitian ini adalah teknik mutual storytelling efektif untuk meningkatkan motivasi belajar peserta didik kelas lima SD. Hasil dari penelitian ini dapat digunakan sebagai referensi bagi guru kelas untuk memperdalam pemahaman pelaksanaan teknik mutual storytelling untuk meningkatkan motivasi belajar bagi peserta didik serta dapat dijadikan referensi bagi peneliti lain untuk berinovasi melakukan penelitian menggunakan teknik mutual storytelling pada bidang layanan yang lain.